SMART TECHNOLOGICAL INNOVATIONS FOR POSTHARVEST LOSS REDUCTION: A REVIEW (FUDMA JOURNAL OF SCIENCES, 2025)
Postharvest losses remain a major threat to food security globally, particularly among low and middle-income countries where the losses of fruits and vegetables are over 30%. This study systematically examines recent technological innovations aimed at mitigating such losses along the postharvest supply chain. Drawing on a diverse range of empirical research, the review examines the performance of emerging technologies like plant-derived edible coatings, modified atmosphere packaging, solar-powered cold storage in mobile containers, evaporative cooling containers and hermetic dry chain systems. These technologies have demonstrated quantifiable gains in the shelf life, nutritional value and marketability of perishable agricultural produce. For instance, application of biodegradable coatings and films derived from essential oils has been associated with 40 to 70% reduction in microbial spoilage of fresh fruits and vegetables. Similarly, solar-powered evaporative coolers and on-the-go cold chain solutions have enhanced storage durations and reduced weight loss in leafy greens and tomatoes in off-grid rural locations. Yet, their successful implementation is usually hindered by systemic constraints such as farmers' lack of expertise, financial limitations and inadequate infrastructure. Field evidence highlights the necessity for context-specific design, farmer-centered training, and inclusive policy assistance. The research finds that optimal outcomes are achieved when smart technologies are implemented in conjunction with cooperative strategies that tackle behavioral, structural, and institutional issues. Propelling smart postharvest solutions will entail ongoing research, public-private partnerships and inclusive innovation pathways that accommodate the realities of smallholder producers.
Keywords: Food security; Technoilogies; Edible coatings; Technology adoption